(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Globalization creates not only economic, political, but also cultural and educational values, which determine the future of humanity. Qualifying knowledge, education, freedom, national self-consciousness, and other values as universal values, the globalization phenomena make us keep pace with the times and respond to the challenges with value approaches. The negative impact of globalization is first of all a threat to social justice and the neglecting of human rights. The higher the awareness of self-recognition and self-improvement is, the more surmountable all the dangers and obstacles in the sphere are. Taking into consideration the value-based approaches to education, we have singled out two perceptions of globalization: globalization as an objective process, which goes hand in hand with the dialogue of regionalization and cultures, educational values ​​ (two sides of one external contradictory phenomenon), and globalization as a unification, a process imposed to the world. As a result of our research, we identified the following value approaches to education: Positive: The demand for continuing education in the era of increasing demands for the quality of human potential; Person-centered education, which emphasizes the learner’s personal characteristics, orientations, interests and goals; The discovery and application of new teaching technologies and methods, which first of all contribute to the development of critical thinking; Knowledge as a means of self-recognition and self-improvement of the highest value, which makes a person a full member of the world community in the context of cross-cultural communication; The formation of a creative and harmonious personality, who is able to make informed decisions, to predict their possible consequences and to feel responsibility for the present and future of the world; Negative: The change of literacy standards determined by the influence of the Internet and the flow of information; The decrease of interest in high level national culture and the loss of ability to understand it, the neglecting of cultural values and traditions, psychological devaluation; Consumer attitude towards values; The lack of humanitarian values and tolerance. Globalization has had many obvious effects on educational and communication systems, changing the way education is delivered and the roles of teachers and students. The development of this technology facilitates the transition from an industrial-based society to an information-based society. At the same time, there is a dark side of globalization and too easy access to new information systems: while the richest countries get richer, the poor get poorer. Thus, the informational and educational gap between the rich and the poor is increasing and not narrowing: economic crises, trade imbalances and structural adjustments have caused a moral crisis in many countries, damaging and severing the basic social and cultural life of many families and communities, leading to the unemployment among youth, suicide, violence, racism, drug abuse and anti-social behavior. In the 21st century, education systems face the double challenge of providing learners with the new knowledge, skills and values ​​needed to be competitive in the global marketplace, while at the same time producing professionals who are also good citizens of their country. So, globalization is a challenge not only to rethink what kind of education a person needs, but also what is its ultimate goal and to what extent it will be directed to social justice.